Financial Literacy in the Digital Era: Analyzing Educational Initiatives and their Impact on Consumer Behavior and Financial Decision-making - Hendri Khuan (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to investigate the relationship between financial literacy and financial education and consumer behavior in making financial decisions in the digital era. To achieve this goal, a literature review was conducted to gather insights on the definition and dimensions of financial literacy, the impact of digitalization on financial transactions, and the interaction between financial literacy and consumer behavior. The research method used is a comprehensive literature review analysis, which involves searching and selecting relevant articles from various sources. The findings show that financial literacy has an important role in shaping consumer behavior and financial decision making, especially in the context of digitalization. The implications of these findings for policymakers, educators, financial institutions, and consumers are also discussed. Future research in the area of ​​financial literacy and education in the digital era should pay more attention to the effectiveness of various financial education interventions, exploration of innovative approaches to address financial literacy challenges in the digital era, as well as longitudinal research to understand the long-term impact of financial education on consumer financial behavior and outcomes .